A randomised, double-blind clinical phase II trial of the efficacy, safety, tolerability and pharmacokinetics of a single dose combination treatment with artefenomel and piperaquine in adults and children with uncomplicated Plasmodium falciparum malaria - Fiona Macintyre; Yeka Adoke; Alfred B. Tiono; Tran Thanh Duong; Ghyslain Mombo-Ngoma; Marielle Bouyou-Akotet; Halidou Tinto; Quique Bassat; Saadou Issifou; Marc Adamy; Helen Demarest; Stephan Duparc; et al. (BMC Medicine, 2017)
Abstract Background The clinical development of a single encounter treatment for uncomplicated malaria has the potential to significantly improve the effectiveness of antimalarials. Exploratory data suggested that the combination of artefenomel and piperaquine phosphate (PQP) has the potential to achieve satisfactory cure rates as a single dose therapy. The primary objective of the study was to determine whether a single dose of artefenomel (800 mg) plus PQP in ascending doses is an efficacious treatment for uncomplicated Plasmodium falciparum malaria in the 'target' population of children ≤ 5 years of age in Africa as well as Asian patients of all ages. Methods Patients in six African countries and in Vietnam were randomised to treatment with follow-up for 42–63 days. Efficacy, tolerability, safety and pharmacokinetics were assessed. Additional key objectives were to characterise the exposure–response relationship for polymerase chain reaction (PCR)-adjusted adequate clinical and parasitological response at day 28 post-dose (ACPR28) and to further investigate Kelch13 mutations. Patients in Africa (n = 355) and Vietnam (n = 82) were included, with 85% of the total population being children < 5 years of age. Results ACPR28 in the per protocol population (95% confidence interval) was 70.8% (61.13–79.19), 68.4% (59.13–76.66) and 78.6% (70.09–85.67) for doses of 800 mg artefenomel with 640 mg, 960 mg and 1440 mg of PQP respectively. ACPR28 was lower in Vietnamese than in African patients (66.2%; 54.55–76.62 and 74.5%; 68.81–79.68) respectively. Within the African population, efficacy was lowest in the youngest age group of ≥ 0.5 to ≤ 2 years, 52.7% (38.80–66.35). Initial parasite clearance was twice as long in Vietnam than in Africa. Within Vietnam, the frequency of the Kelch13 mutation was 70.1% and was clearly associated with parasite clearance half-life (PCt1/2). The most significant tolerability finding was vomiting (28.8%). Conclusions In this first clinical trial evaluating a single encounter antimalarial therapy, none of the treatment arms reached the target efficacy of > 95% PCR-adjusted ACPR at day 28. Achieving very high efficacy following single dose treatment is challenging, since > 95% of the population must have sufficient concentrations to achieve cure across a range of parasite sensitivities and baseline parasitaemia levels. While challenging, the development of tools suitable for deployment as single encounter curative treatments for adults and children in Africa and to support elimination strategies remains a key development goal. Trial registration ClinicalTrials.gov, NCT02083380 . Registered on 7 March 2014.